Legal Protection of Land Rights Ownership Through the Rechtsverwerking Institution - Kim Ahlam; Adonia Ivone Laturettte; Pieter Radjawane (LUTUR Law Journal, 2025)
Disputes related to land always increase in number to cause many cases, one of which is the ownership of land rights through the concept of rechtsverwerking (Releasing Rights) who have obtained a certificate of land rights, even though the provisions of laws and regulations and in several Supreme Court Jurisprudence have accommodated it, but the party who obtains land rights through the concept in question has not received legal protection against The application of the concept. The research method used in writing this thesis The author uses a normative juridical research method with an analytical descriptive research type of laws and regulations and uses primary, secondary and tertiary sources of legal materials through the procedure of collecting legal materials and analyzing legal materials to obtain conclusions. The results of the study found that the principle of good faith in the ownership of land rights through the concept of rechtsverwerking can be applied to the possession of land by the party who controls the land for a reasonable period of time in a real way with good etiquette, then the person concerned can register it to obtain a certificate of ownership more than 5 (Five) years after it was issued, then the previous owner cannot file an objection and/or claim his rights again, because based on the concept of rechtsverwerking the person concerned is considered to have relinquished his rights or relinquished his rights thus his rights are lost and/or deleted, therefore the ownership of land rights through the concept of rechtsverwerking must receive legal protection. The form of legal protection for the ownership of land rights based on the concept of rechtsverwerking cannot be separated from the issue of justice in the implementation of the law itself. Protection for land rights holders based on rechtsverwerking institutions in the form of preventive protection and repressive protection.